Jerusalem Crucified, Jerusalem Risen : the Resurrected Messiah, the Jewish People, and the Land of Promise. - Kinzer Mark S.
The good news (euangelion) of the crucified and risen Messiah was proclaimed first to Jews in Jerusalem, and then to Jews throughout the land of Israel. In Jerusalem Crucified, Jerusalem Risen, Mark Kinzer argues that this initial audience and geographical setting of the euangelion is integral to the eschatological content of the message itself. While the good news is universal in concern and cosmic in scope, it never loses its particular connection to the Jewish people, the city of Jerusalem, and the land of Israel. The crucified Messiah participates in the future exilic suffering of his people, and by his resurrection offers a pledge of Jerusalem's coming redemption. Basing his argument on a reading of the Acts of the Apostles and the Gospel of Luke, Kinzer proposes that the biblical message requires its interpreters to reflect theologically on the events of post-biblical history. In this context he considers the early emergence of Rabbinic Judaism and the much later phenomenon of Zionism, offering a theological perspective on these historical developments that is biblically rooted, attentive to both Jewish and Christian tradition, and minimalist in the theological constraints it imposes on the just resolution of political conflict in the Middle East.
Keywords: Temple of Jerusalem (Jerusalem) -- In the Bible.; Bible. -- Luke -- Criticism, interpretation, etc.; Bible. -- Acts -- Criticism, interpretation, etc.; Temple of Jerusalem (Jerusalem); Bible. -- Acts; Bible. -- Luke; Israel (Christian theology) -- Biblical teaching.; Eschatology.; Jews -- Restoration.; Messianic Judaism.; Zionism.; Jerusalem.; Israël (Théologie chrétienne) -- Enseignement biblique.; Juifs -- Restauration.; Judaïsme messianique.; RELIGION -- Christianity -- Denominations.; Eschatology; Israel (Christian theology) -- Biblical teaching; Jews -- Restoration; Messianic Judaism; Temple of Jerusalem (Jerusalem) in the Bible; Zionism; Middle East -- Jerusalem; Electronic books.; Criticism, interpretation, etc.